Scaling up and implementing the digital Survivorship Passport tool in routine clinical care – The European multidisciplinary PanCareSurPass project - Filbert, Anna-Liesa; Kremer, Leontien; Ladenstein, Ruth; Chronaki, Catherine; Degelsegger-Márquez, Alexander; van der Pal, Heleen; Bardi, Edit; Uyttebroeck, Anne; Langer, Thorsten; Muraca, Monica; Nieto, Adela Cañete; Rascon, Jelena; et al. (European journal of cancer (1990), 2024)
Childhood cancer survivors (CCS), of whom there are about 500,000 living in Europe, are at an increased risk of developing health problems [1–6] and require lifelong Survivorship Care. There are information and knowledge gaps among CCS and healthcare providers (HCPs) about requirements for Survivorship Care [7–9] that can be addressed by the Survivorship Passport (SurPass), a digital tool providing CCS and HCPs with a comprehensive summary of past treatment and tailored recommendations for Survivorship Care. The potential of the SurPass to improve person-centred Survivorship Care has been demonstrated previously [10,11]. The EU-funded PanCareSurPass project will develop an updated version (v2.0) of the SurPass allowing for semi-automated data entry and implement it in six European countries (Austria, Belgium, Germany, Italy, Lithuania and Spain), representative of three infrastructure healthcare scenarios typically found in Europe. The implementation study will investigate the impact on person-centred care, as well as costs and processes of scaling up the SurPass. Interoperability between electronic health record systems and SurPass v2.0 will be addressed using the Health Level Seven (HL7) International interoperability standards. PanCareSurPass will deliver an interoperable digital SurPass with comprehensive evidence on person-centred outcomes, technical feasibility and health economics impacts. An Implementation Toolkit will be developed and freely shared to promote and support the future implementation of SurPass across Europe. PanCareSurPass is a novel European collaboration that will improve person-centred Survivorship Care for CCS across Europe through a robust assessment of the implementation of SurPass v2.0 in different healthcare settings. •SurPass addressing knowledge gaps regarding Survivorship Care requirements.•SurPass v2.0 will improve person-centred Survivorship Care for CCS across Europe.•SurPass v2.0 as an interoperable digital tool.•Generating evidence on person-centred outcomes, feasibility and health economics.•Promoting uptake of the SurPass via freely available Implementation Toolkit.